Uptake and use of gender research methodologies and tools from the project “GENNOVATE” by agriculture researchers worldwide - CGIAR Research Program on Wheat (2018)
GENNOVATE is a global comparative research initiative that addresses the question of how gender norms and agency influence men, women, and youth to adopt innovation in agriculture and natural resource management. Findings from this work are being taken up by international agricultural researchers and impacting how they work and how they target their work to better reach men, women and youth.